Mesenteric ischemia: conceptions and approaches to an emergency (Research, Society and Development, 2023)
This study aimed at the pathological understanding of MI, the contributors to the evolution of the ischemia process and the health considerations of emergency situations. This is a critical and analytical narrative review of research on the principles of MI, bearing in mind the lethality levels of the disease and the most comfortable prognosis for the patient. A search for articles was carried out in the Medical Literature Analysis and Retrievel System Online, Scientific Electronic Library Online and PubMed databases, with the following Health Sciences Descriptors: Artery; General surgery; Management; Trauma. Selecting articles between the periods of 2002 to 2023, in English, Portuguese and Spanish, to increase the level of transmission and the quality of the review. AI proved to be a highly lethal pathology, mainly related to mortality rates and the time taken for diagnosis and treatment. It should be understood that, currently, medicine is constantly seeking evolution. However, in the clinical condition of abdominal pain, a diagnostic suspicion of MI is indicated and, when available, an angiotomography of the abdomen should be performed, in order to perform timely therapy. In this context, exploratory laparotomy remains the classic management of choice and recommended.